2002
DOI: 10.1097/01.lab.0000018827.78602.f4
|View full text |Cite
|
Sign up to set email alerts
|

Chymase Participates in Chronic Dermatitis by Inducing Eosinophil Infiltration

Abstract: SUMMARY:An epicutaneous application of 2,4-dinitrofluorobenzene (DNFB) to a mouse ear caused a transient skin swelling, and the repetition of the challenge enlarged the contact dermatitis. The repeated challenge with DNFB also induced eosinophil infiltration on the application site. Administration of a chymase inhibitor significantly inhibited the ear swelling as well as eosinophil accumulation. An intradermal injection of human chymase to the mouse ear also elicited transient skin swelling and eosinophil infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 28 publications
1
27
1
1
Order By: Relevance
“…These in vivo studies indicate that either chymase activates a resident, dormant chemokine, or that chymase itself is chemotactic. Although chymase was not found to be chemotactic in our study, two groups reported that this enzyme was chemotactic for human leukocytes in vitro (41,42,45). However, enzymatic activity was required for chemoattraction in each of these studies, raising the possibility that the actual chemoattractant might have been a chymase-derived cleavage fragment of an inactive chemokine secreted by the cells.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…These in vivo studies indicate that either chymase activates a resident, dormant chemokine, or that chymase itself is chemotactic. Although chymase was not found to be chemotactic in our study, two groups reported that this enzyme was chemotactic for human leukocytes in vitro (41,42,45). However, enzymatic activity was required for chemoattraction in each of these studies, raising the possibility that the actual chemoattractant might have been a chymase-derived cleavage fragment of an inactive chemokine secreted by the cells.…”
Section: Discussioncontrasting
confidence: 45%
“…Injection of human chymase into mouse ear also resulted in polymorphonuclear cell recruitment (41,42). Moreover, a chymase inhibitor significantly impaired cell recruitment in several experimentally induced and natural dermatitis models, indicating that chymase plays a role in dermal inflammatory reactions (41)(42)(43)(44). These in vivo studies indicate that either chymase activates a resident, dormant chemokine, or that chymase itself is chemotactic.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These lines of evidence suggested a new model system for antigen-induced dermatitis. Alternatively, dermatitis can also be induced in NC mice by a hapten, such as 2,4-dinitrofluorobenzene (DNFB) (Tomimori et al, 2002, Tomimori et al, 2005, trinitrochlorobenzene (TNCB) (Taniguchi et al, 2003), or FITC (Hvid et al, 2009). Using these induced dermatitis models in NC mice, extensive surveys for therapeutic agents, both chemicals and herbal medicine, have been performed (Kobayashi et al, 2003, Lee et al, 2007, Jiang et al, 2009, Joo et al, 2009, Lee et al, 2010, Sung et al, 2011a, Sung et al, 2011b, Wu et al, 2011.…”
Section: Details Of the Nc Modelmentioning
confidence: 99%
“…These include induction of microvascular leakage in skin of guinea pig [26] , stimulation of inflammatory cell accumulation in peritoneum of mouse [27,28] and modulation of mast cell degranulation [29,30] , indicating that they may be key mediators of allergic inflammation and promising targets for diagnosis and therapeutic intervention [31][32][33][34][35] . However, little is known about the function of hMC-CP except for its ability to cleave angiotension I [13] .…”
Section: Introductionmentioning
confidence: 99%